Northern Europe (Göttingen V&R unipress, Vienna Univ. Press, 2014)
The project “Religious Education at Schools in Europe” (REL-EDU), which is divided up into six volumes (Central Europe, Western Europe, Northern Europe, Southern Europe, South-Eastern Europe, Eastern Europe), aims to research the situation with regard to religious education in Europe. The third volume outlines the organisational form of religious education in the countries of Northern Europe (Denmark, Sweden, Finland, Norway, Estonia, Lithuania, Latvia, Iceland). This is done on the basis of thirteen key issues, which allows specific points of comparison between different countries in Europe. Thereby the volume focusses the comparative approach and facilitates further research into specific aspects of the comparison.
Literaturangaben
Online-Ausg.
Keywords: Religious Education; Northern Europe; Comparative Research; Education; Religiöse Bildung; Schule; Europa; Religionsunterricht; Aufsatzsammlung